Construction of influencing factor model for high-quality green development of Chinese industrial enterprises - Fang, Zhen; Yang, Can; Song, Xiaowei (Frontiers in Environmental Science, 2022)
The strategic planning and decision-making of the government in the combination of high-quality development and green development has had a far-reaching impact on the development of industrial enterprises. This paper uses the grounded theory to build a theoretical framework model of the influencing factors of high-quality green development of industrial enterprises. The data are based on policy documents, policy interpretations, official public opinion and other original text materials related to the high-quality green development of Chinese industrial enterprises. The research finds that the influencing factors of high-quality green development of industrial enterprises can be divided into three dimensions, including environmental dimension, enterprise dimension and process dimension. Among them, the enterprise dimension is the most core dimension and directly affects the high-quality green development of industrial enterprises. Different parts (six parts) in each dimension are connected together to form a circular chain of high-quality green development of industrial enterprises. There is also an interaction mechanism within each part.